Sodno varstvo referenduma - Sovdat, Jadranka (Pravnik, 2013)
The legislative referendum is an institution entailing the direct execution of democratic power. In the Slovenian constitutional order it has the form of a subsequent referendum by which a particular proposed law is accepted or rejected, thus it is a correction and a form of supervision over parliamentary decision-making. In order to conduct a referendum on a particular law, there are three types of rights that are exercised according to a certain chronological order. The following two rights are especially important: the right to require that a referendum be called, which is only granted to a certain number of voters, in accordance with the latest amendment to the Constitution, and the right to vote in a referendum, which is granted to all voters. In order to ensure the effectiveness of these rights, judicial protection must be ensured, which differs according to the nature of the individual rights. The legislature should devote appropriate and comprehensive attention to the regulation of the judicial protection of referendum rights. Due to the latest constitutional amendment, within one year the National Assembly must amend the statutory provisions on the constitutional protection of the right to require that a legislative referendum be called. The National Assembly should establish a uniform legal remedy for the protection of this right granted to the proposer of a referendum, on the basis of which the Constitutional Court would decide on the admissibility of the referendum. In addition to the amendment of the statutory regulation of the protection of the right to require that a referendum be called, the legislature should also amend the judicial protection of the right to vote in a referendum. Such amendment is not required by the constitutional amendment, but by the inappropriate regulation in force. The legislature should introduce a referendum dispute that would be, similarly as electoral disputes, intended to ensure the legitimacy of the voters' will expressed in a referendum and consequently to ensure the legitimacy of the referendum decision.
Keywords: pravice; pravna ureditev; referendum